Internal security operations and human rights abuses in Nigeria: issues and challenges (2014)
The most outstanding challenge to the Nigerian state since the beginning of the twenty- first century is probably the proliferation of internal conflicts. This is primarily because they impede the growth of democracy and threaten national security. In order to maintain peace and security, the military is given a constitutional role in managing internal conflicts through internal security operations when the police is overwhelmed. However, the military at times misuse the constitutional powers by violating the rights of the civilian population. This paper examines the connection between internal security operations and human rights abuses in Nigeria. The major direction is to provide a deeper understanding of the constitutional role of the military in the management of internal conflicts, while also looking at the challenges and the prospects for non-violation of human rights of civilian population. The paper concludes with some recommendations on how the military can be involved in internal security operations without violating citizens’ human rights